The dark side of politics essays on the unpleasant realities of political life - Ginsberg, Benjamin (New York Routledge, 2024)
Scholarly essays that explore the unpleasant realities of modern American politics
Violence -- War -- Rewriting history -- Bureacracy -- Duplicity -- Surveillance and secrecy -- Legitimacy -- Epilogue: Death.
Includes bibliographical references and index
Keywords: Political science -- United States; Political violence -- United States; United States -- Politics and government -- History